To what extent is blood a reasonable surrogate for brain in gene expression studies: estimation from mouse hippocampus and spleen - Davies, Matthew N.; Lawn, Sarah; Whatley, Steven; Fernandes, Cathy; Williams, Robert W.; Schalkwyk, Leonard C. (Frontiers in Neuroscience, 2009)
Microarrays are designed to measure genome-wide differences in gene expression. In cases where a tissue is not accessible for analysis (e.g. human brain), it is of interest to determine whether a second, accessible tissue could be used as a surrogate for transcription profiling. Surrogacy has applications in the study of behavioural and neurodegenerative disorders. Comparison between hippocampus and spleen mRNA obtained from a mouse recombinant inbred panel indicates a high degree of correlation between the tissues for genes that display a high heritability of expression level. This correlation is not limited to apparent expression differences caused by sequence polymorphisms in the target sequences and includes both cis and trans genetic effects. A tissue such as blood could therefore give surrogate information on expression in brain for a subset of genes, in particular those co-expressed between the two tissues, which have heritably varying expression.